ROLE OF NEGATIVE INSPIRATORY FORCE INDEX (NIF) IN PREDICTING WEANING SUCCESS FROM MECHANICAL VENTILATOR IN INTENSIVE CARE UNIT (ICU) PATIENTS (The Research of Medical Science Review, 2025)
Background: The process of determining the appropriate timing for extubation in intubated patients is critical challenge in intensive care units. Negative Inspiratory Force (NIF) index is recommended as a predictor for successful weaning from mechanical ventilation. However, its predictive value, particularly in the Pakistani public sector intensive care population, is not well-documented. The NIF showed greater Sensitivity and Specificity and plays a crucial role in assessing the likelihood of successful weaning from mechanical ventilation in the clinical and surgical patients and enhance the accuracy of ventilator liberation decisions. Aim: Here we aimed to determine how measurements of negative inspiratory force (NIF) can predict the success of weaning patients from mechanical ventilation in public sector intensive care units (ICUs) and to establish threshold values for clinical use. Methods: This cross sectional study was conducted at the Intensive care units of Lady Reading Hospital Peshawar from September 2024 to December 2024. A total of 140 patients aged 18 -70 years, receiving mechanical ventilation through endotracheal tube and satisfying the criteria to be readiness to begin were included. Data were collected using a structured questionnaire and analysed by using SPSS V22. NIF cut-off values for both groups were also calculates and analyse. Descriptive statistics were presented as frequency and percentages, while for inferential statistics chi-square tests were applied to identify association between the NIF indexes with outcomes of the weaning process. Results: The Success rate of the entire weaning process (SBT & extubation) was 76.4% (107/140). The median NIF values were -23.0 cmH20 (interquartile range IQR, -28.0 to -18.0 cmH20) in the successful weaning group and -19.0 cmH20 (IQR,-24.0 to -14.0) in the weaning failure group (P<0.001). Accordingly a NIF value of -22.0 cmH20 is predictor for weaning success in ICU patients. Conclusion: A NIF cut-off threshold of -22.0 cmH20 can be used as predictor of weaning success in ventilated patients of public sector ICUs of Pakistan